Revealing the morphological peculiarities of Y₃Al₅O₁₂:Nd laser ceramics by ion beam sputtering - Vovk, O.M.; Chayka, M.A.; Mateychenko, P.V.; Yavetskiy, R.P.; Kosyanov, D.Yu.; Parkhomenko, S.V. (Functional Materials, 2013)
The morphological peculiarities of Y₃Al₅O₁₂:Nd laser ceramics prepared by vacuum sintering of co-precipitated nanopowders have been revealed by ion beam sputtering of the ceramics surface. Inclusions with a cross section up to 5 μ m located between the grain boundaries as well as pores and grain boundaries were detected on the surface of Y₃Al₅O₁₂:Nd ceramics treated by ion sputtering since sputtering rate of these inclusions is much lower compared to bulk of ceramics. Qualitative elemental composition of inclusions is same as that of Y₃Al₅O₁₂:Nd ceramics. It was suggested that the inclusions were formed as a result of local deviation from stoichiometry Y₃Al₅O₁₂ during processing of ceramics and have different phase composition compared to the parent garnet phase. The concentration of revealed inclusions which is higher the one of pores.